Відновлення спектрального типу граничних розподілів у динамічних системах конфлікту - Кошманенко, В.Д. (Український математичний журнал, 2007)
Получены условия восстановления чистого спектрального типа (чисто точечного, чисто абсолютно непрерывного или чисто сингулярно непрерывного) в граничных распределениях динамических систем с композицией альтернативного конфликта. В частности, показано, что точечный спектр можно регенерировать исходя из состояний с чисто сингулярно непрерывным спектром. Regeneration conditions of a pure spectral type (purely point, purely absolutely continuous, or purely
singularly continuous) in limiting distributions of dynamical systems with the alternative conflict
composition are obtained. In particular, it is shown, that the point spectrum may be regenerated starting
from states with purely singularly continuous spectrum.